The Representation of Moroccans in Spain in Ramito de hierbabuena, by Gerardo Muñoz Lorente - Ouahib, Mohammed (2024)
Since the mid-nineties of the 20th century, many works have been published about the arrival of irregular migrants on boats, especially from Morocco in search of a dignified future, with which Spain have gone from being a country that historically sends emigrants to another that receives them. The fundamental objective of this is to highlight the representation of Moroccans in Spain, who generally suffer from social exclusion and discrimination, which creates important consequences for their integration into the host society. In order to carry out that objective, this article analyzes the representation of Moroccans in Spain in the novel Ramito de hierbabuena by Gerardo Muñoz Lorente, throught the method of critical discourse analysis, whose approach studies the power mechanisms that exist among emigrants.